Effects of different intervention combined with resistance training on musculoskeletal health in older male adults with sarcopenia: A systematic review - Carcelén-Fraile, María del Carmen; Lorenzo-Nocino, María Florencia; Afanador-Restrepo, Diego Fernando; Rodríguez-López, Carlos; Aibar-Almazán, Agustín; Hita-Contreras, Fidel; Achalandabaso-Ochoa, Alexander; Castellote-Caballero, Yolanda (Frontiers in Public Health, 2023)
Objectives: Nowadays, there is a significant increase in the elderly population in many countries around the world, and sarcopenia is one of the most common consequences of this with resistance training being one of the best treatments. Hence, this systematic review was conducted to determine what are the effects of different combinations of resistance training-based interventions on the musculoskeletal health of older male adults with sarcopenia Methods: This systematic review was performed following the PRISMA 2020 guidelines. The search was performed between February and August 2022 in three electronic databases: Pubmed (MEDLINE), Web of Science (WOS) and Scopus employing different keywords combined with Boolean operators. Only 13 articles were included out of the initial 1019. Results: The articles studied the effects of resistance training combined with other interventions, 6 articles combined it with protein and vitamin supplementation, 4 with protein supplements only, while 3 combined it with aerobic training, finding beneficial results mainly on strength, functionality, and body composition. Conclusion: Resistance Training combined with Aerobic Training or nutritional supplements has better effects than Resistance Training alone in older male adults with sarcopenia.